2020
DOI: 10.1002/ece3.6404
|View full text |Cite
|
Sign up to set email alerts
|

“A cleaner break”: Genetic divergence between geographic groups and sympatric phenotypes revealed in ballan wrasse (Labrus bergylta)

Abstract: Capture and long‐distance translocation of cleaner fish to control lice infestations on marine salmonid farms has the potential to influence wild populations via overexploitation in source regions, and introgression in recipient regions. Knowledge of population genetic structure is therefore required. We studied the genetic structure of ballan wrasse, a phenotypically diverse and extensively used cleaner fish, from 18 locations in Norway and Sweden, and from Galicia, Spain, using 82 SNP markers. We detected tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 78 publications
4
11
0
Order By: Relevance
“…In a recent study, Mattingsdal and colleagues (2020) showed that the current-day population structure of corkwing wrasse in Scandinavia characterized by a substantial division between western and southern Scandinavia can mainly be explained with past demographic events followed by reproductive isolation and genetic drift. Similar colonization history was newly suggested for ballan wrasse (Seljestad et al 2020). Unlike corkwing and ballan wrasse for which Scandinavian western and southern populations are quite isolated (but see Mattingsdal et al 2020 proving some gene ow across the genetic break), the Scandinavian goldsinny population is characterized by extensive gene ow following oceanic currents, weak general population structure, increasing genetic divergence with oceanographic distance (i.e.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In a recent study, Mattingsdal and colleagues (2020) showed that the current-day population structure of corkwing wrasse in Scandinavia characterized by a substantial division between western and southern Scandinavia can mainly be explained with past demographic events followed by reproductive isolation and genetic drift. Similar colonization history was newly suggested for ballan wrasse (Seljestad et al 2020). Unlike corkwing and ballan wrasse for which Scandinavian western and southern populations are quite isolated (but see Mattingsdal et al 2020 proving some gene ow across the genetic break), the Scandinavian goldsinny population is characterized by extensive gene ow following oceanic currents, weak general population structure, increasing genetic divergence with oceanographic distance (i.e.…”
Section: Discussionsupporting
confidence: 80%
“…Genetic studies of ballan wrasse (Labrus bergylta) have concentrated on investigation of population structure on large geographic scales (D'Arcy et al 2013; Almada et al 2017), and on genetic divergence of different morphotypes (Quintela et al2016;Almada et al 2016). A newly published study by Seljestad et al (2020) revealed subdivision on a more local scale as well, dividing the Scandinavian ballan wrasse population into two distinct genetic clusters. An early genetic study of goldsinny wrasse with allozyme markers showed signi cant differences between the southern and mid-Norway (Sundt & Jørstad 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Mattingsdal et al [71] showed that the current-day population structure of corkwing wrasse in Scandinavia characterized by a substantial division between western and southern Scandinavia can mainly be explained with past demographic events followed by reproductive isolation and genetic drift. Similar colonization history was newly suggested for ballan wrasse [84]. Unlike corkwing and ballan wrasse for which Scandinavian western and southern populations are quite isolated (but see [71] proving some gene flow across the genetic break), the Scandinavian goldsinny population is characterized by extensive gene flow following oceanic currents, weak general population structure, increasing genetic divergence with oceanographic distance (i.e.…”
Section: Discussionsupporting
confidence: 59%
“…Genetic studies of ballan wrasse (Labrus bergylta) have concentrated on investigation of population structure on large geographic scales [4,21], and on genetic divergence of different morphotypes [3,80]. A newly published study by Seljestad et al [84] revealed subdivision on a more local scale as well, dividing the Scandinavian ballan wrasse population into two distinct genetic clusters. An early genetic study of goldsinny wrasse with allozyme markers showed significant differences between the southern and mid-Norway [92].…”
Section: Introductionmentioning
confidence: 99%
“…This example clearly illustrates the importance of ancestral divergence and the trapping of a secondary contact zone at a density trough. Notably, population-genetic data show the presence of a contact zone in a taxonomically close and ecologically very similar species, ballan wrasse (Labrus bergylta), overlapping with the corkwing wrasse contact [50] (Figure 2).…”
Section: Trends Trends In In Ecology Ecology and Evolution Evolutionmentioning
confidence: 99%